Unleashing Your Data with Power BI Machine Learning and OpenAI Embark on a Data Adventure and Turn Your Raw Data into Meaningful Insights - Beaumont, Greg (Packt Publishing, Limited, 2023)
Unleash the full potential of Power BI with the integration of AI and machine learning techniques using OpenAI Purchase of the print or Kindle book includes a free PDF eBook Key Features Take flight with Power BI machine learning and OpenAI using hands-on examples from the FAA airline data Unlock the full potential of Power BI for advanced analytics using OpenAI Design stunning data presentations, seamless integration of machine learning tools and technologies with OpenAI Book Description Microsoft Power BI is the ultimate solution for businesses looking to make data-driven decisions and unlock the full potential of their data. Unleashing Your Data with Power BI Machine Learning and OpenAI is designed for data scientists and BI professionals seeking to improve their existing solutions and workloads using AI. The book explains the intricacies of the subject by using a workshop-style data story for data ingestion, data modeling, analytics, and predictive analytics with Power BI machine learning. Along the way, you'll learn about AI features, AI visuals, R/Python integration, and OpenAI integration. The workshop-style content allows you to practice all your learnings in real-life challenges and gain hands-on experience. Additionally, you'll gain an understanding of AI/ML, step by step, with replicable examples and references. From enhancing data visualizations to building SaaS Power BI ML models, and integrating Azure OpenAI, this book will help you unlock new capabilities in Power BI. By the end of this book, you'll be well-equipped to build ML models in Power BI, plan projects for both BI and ML, understand R/Python visuals with Power BI, and introduce OpenAI to enhance your analytics solutions. What you will learn Discover best practices for implementing AI and ML capabilities in Power BI along with integration of OpenAI into the solution Understand how to integrate OpenAI and cognitive services into Power BI Explore how to build a SaaS auto ML model within Power BI Gain an understanding of R/Python integration with Power BI Enhance data visualizations for ML feature discovery Discover how to improve existing solutions and workloads using AI and ML capabilities in Power BI with OpenAI Acquire tips and tricks for successfully using AI and ML capabilities in Power BI along with integration of OpenAI into the solution Who this book is for This book is for data science and BI professionals looking to expand their skill sets into Power BI machine learning and OpenAI. This book is also useful for data scientists, data analysts, and IT professionals who want to learn how to incorporate OpenAI into Power BI for advanced experience.